2017
DOI: 10.1016/j.rpor.2016.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Long term clinical toxicity of radiation therapy in prostate cancer patients with Inflammatory Bowel Disease

Abstract: Radiation induced bowel toxicity a b s t r a c tAim: The study's aim was to examine the clinical impact of radiation therapy (RT) on GI toxicity in Inflammatory Bowel Disease (IBD) patients.Background: IBD has long been considered a risk factor for increased bowel toxicity from RT;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 25 publications
1
17
0
Order By: Relevance
“…In addition, in patients undergoing CMT, inferior outcomes were noted in those with hydronephrosis [19]. There have been mixed reports of patients with inflammatory bowel disease (IBD) being at increased risk of GI toxicities with radiation therapy, but a report by Gestaut et al reviewed patients over a 23 year period in patients with IBD and prostate cancer who underwent radiation therapy and found minimal GI toxicity in the IMRT era [20]. Therefore, just as surgery requires preoperative evaluation, review of patient candidacy for CMT is warranted as well.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in patients undergoing CMT, inferior outcomes were noted in those with hydronephrosis [19]. There have been mixed reports of patients with inflammatory bowel disease (IBD) being at increased risk of GI toxicities with radiation therapy, but a report by Gestaut et al reviewed patients over a 23 year period in patients with IBD and prostate cancer who underwent radiation therapy and found minimal GI toxicity in the IMRT era [20]. Therefore, just as surgery requires preoperative evaluation, review of patient candidacy for CMT is warranted as well.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the patient presented in this case was not on pharmacologic therapy and, as such, had a favorable prognosis with regards to toxicity stemming from RT. Similarly, Gestaut et al reported no incidences of > Grade 1 diarrhea or proctitis following IMRT without any post-radiation strictures at an average follow-up of 12 years [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is especially relevant for PCa patients with inflammatory bowel disease (IBD), as IBD is considered to be a relative contraindication of RT because of the possible increased risk of GI toxicity and subsequent disease exacerbation [ 2 ]. With the advent of intensity-modulated radiation therapy (IMRT), less irradiation to the surrounding tissue and acceptable GI toxicity rates can be achieved as compared to conventional RT techniques for IBD patients with PCa [ 3 ]. Additionally, the recent introduction of hydrogel rectal spacers in clinical practice provides a novel approach for further minimizing radiation to the rectum for PCa patients at a higher risk of late toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…Radiation enteritis and proctitis are the most serious side effects of abdominopelvic cancers in the gastrointestinal system [ 2 ]. In addition to these cancers, the lower parts of the gastrointestinal system are affected by exposure to radiation by radiotherapy for other tumors such as prostate, colorectal and urinary cancers [ 3 , 4 ]. Exposure of the lower parts of the intestine including ileum and colon, to high doses of ionizing radiation may lead to acute and late effects such as damage to villous, inflammation, pain, ulcer and bleeding.…”
Section: Introductionmentioning
confidence: 99%